Effect of perforation on drying kinetics of Rosa rubiginosa fruits - Ohaco Dominguez, Elizabeth Haydee; De Michelis, Antonio; Lozano, Jorge Enrique (Asian Academic Research Associates, 2018)
The effect of perforation and drying air operating variables on drying kinetics of Rosa rubiginosa fruits was investigated. Before drying, half the fruit sample was perforated in order to speed up the drying process. Samples were dried at air temperatures: 60, 70, and 80ºC, air velocity: 1 m/s and 5 m/s, and relative humidity: 5% and 50%. Among the studied factors, drying temperature and perforation were found to affect the drying of those fruits. The drying kinetics was fitted by two mathematical models, Becker and Fick's second law, considering fruit shrinkage during drying. Both models satisfactorily predict the fruit drying, in perforated and non-perforated fruits. The effective diffusivity coefficients (Deff) increased 20 % with the perforation applied to the fruit, except at 50ºC. This indicates that perforation at low temperatures of drying was not effective.Temperature dependence of Deff were: for nonperforated fruits, Ea = 48.91 kJ/mol (analytical solution) and 50.25 kJ/mol (Becker), and for perforated fruits, Ea = 37.04 kJ/mol (analytical solution) and 41.16 kJ/mol (Becker).